Cytotoxic Compounds from the Leaves of Garcinia polyantha. Issue 6 (June 2014) - Lannang, Alain Meli; Tatsimo, Simplice J. N.; Fouotsa, Hugues; Dzoyem, Jean Paul; Saxena, Ajit Kumar; Sewald, Norbert
Abstract A new compound, named banganxanthone C (=12‐(1, 1‐dimethylprop‐2‐en‐1‐yl)‐5, 10‐dihydroxy‐9‐methoxy‐2‐methyl‐2‐(4‐methylpent‐3‐en‐1‐yl)‐2H, 6H‐pyrano[3, 2‐b]xanthen‐6‐one; 4), together with five known compounds, were isolated from the leaves of Garcinia polyantha. The structures of the compounds were elucidated on the basis of 1D‐ and 2D‐NMR spectroscopy. Among the known compounds, two were xanthones, one was a pentacyclic triterpene, one sterol, and one benzophenone derivative. Isoxanthochymol (2) and 4‐[(2E)‐3, 7‐dimethylocta‐2, 6‐dien‐1‐yl]‐1, 5, 8‐trihydroxy‐3‐methoxy‐9H‐xanthen‐9‐one (3) exhibited significant antiproliferative activity against the leukemia cell line TPH‐1 with IC50 inhibition values of 1.5 and 2.8 μg/ml, respectively. The cytotoxic activity was found to be related to apoptosis induction.